2014
DOI: 10.1007/s00253-013-5381-0
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of EPA/DHA omega-3 fatty acid production by Lactococcus lactis subsp. cremoris MG1363

Abstract: Eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have been shown to be of major importance in human health. Therefore, these essential polyunsaturated fatty acids have received considerable attention in both human and farm animal nutrition. Currently, fish and fish oils are the main dietary sources of EPA/DHA. To generate sustainable novel sources for EPA and DHA, the 35-kb EPA/DHA synthesis gene cluster was isolated from a marine bacterium, Shewanella baltica MAC1. To streamline the introduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…These results are concordant with previous investigations that have shown an antimicrobial antiseptic effect of PUFAs extracts [33], mainly EPA and DHA extracts found naturally in many marine organisms [44,45]. In addition, and beyond their antimicrobial activity (confirmed in the present study), it should be highlighted that PUFAs have also demonstrated anti-inflammatory [25][26][27][28][44][45][46][47] and antioxidant [48] properties. A dense bacterial population could be observed on the HA discs treated with PBS (A), forming discontinuous layers of bacteria bonded to the discs.…”
Section: Discussionsupporting
confidence: 93%
“…These results are concordant with previous investigations that have shown an antimicrobial antiseptic effect of PUFAs extracts [33], mainly EPA and DHA extracts found naturally in many marine organisms [44,45]. In addition, and beyond their antimicrobial activity (confirmed in the present study), it should be highlighted that PUFAs have also demonstrated anti-inflammatory [25][26][27][28][44][45][46][47] and antioxidant [48] properties. A dense bacterial population could be observed on the HA discs treated with PBS (A), forming discontinuous layers of bacteria bonded to the discs.…”
Section: Discussionsupporting
confidence: 93%
“…Thus, the phenotype is consistent with the phylogenetic trees con- Derived from genomic sequence data. pfaA (5) indicates that there were five ACP binding domains based upon the predicted protein product for pfaA. The numbers in red indicate numbers of base pairs.…”
Section: Resultsmentioning
confidence: 99%
“…A safe and potentially inexpensive solution to this demand was triggered by the discovery in 1986 by DeLong and Yayanos (2) that certain deep-sea marine bacteria, and not just eukaryotic microbes (3), could produce omega-3 fatty acids such as EPA and/or DHA. This discovery suggested that marine bacteria could be a source of omega-3 fatty acids either by direct isolation from the bacteria or through genetic engineering allowing overproduction in numerous hosts (1,4,5). Soon after the initial discovery, many laboratories also isolated omega-3 fatty acid-producing bacteria from ocean depths, from colder regions of the ocean, and from gastrointestinal tracts of omega-3 fatty acid-containing marine fish, such as mackerel, or shellfish (6)(7)(8)(9).…”
mentioning
confidence: 99%
“…baltica MAC1 (0.4% of total fatty acids) [ 18 , 21 ]. In addition, expression of the Shewanella pfa gene cluster in food-grade Lactococcus lactis successfully produced both DHA (1.35 mg/g CDW) and EPA (0.12 mg/g DCW) [ 22 ]. Compared to the published data, the DHA content of recombinant E .…”
Section: Resultsmentioning
confidence: 99%